2014
DOI: 10.1371/journal.pone.0088058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peripheral 5-HT on Glucose and Lipid Metabolism in Wether Sheep

Abstract: In mice, peripheral 5-HT induces an increase in the plasma concentrations of glucose, insulin and bile acids, and a decrease in plasma triglyceride, NEFA and cholesterol concentrations. However, given the unique characteristics of the metabolism of ruminants relative to monogastric animals, the physiological role of peripheral 5-HT on glucose and lipid metabolism in sheep remains to be established. Therefore, in this study, we investigated the effect of 5-HT on the circulating concentrations of metabolites and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 50 publications
2
19
1
1
Order By: Relevance
“…Interestingly, in an experiment conducted in wethers that were fasted for 24 h, i.v. treatment with serotonin, not 5-HTP, increased both glucose and insulin concentrations for 1 h post-treatment (Watanabe et al 2014). This indicates that serotonin may act differently depending on the stage of the energy balance of the animal.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Interestingly, in an experiment conducted in wethers that were fasted for 24 h, i.v. treatment with serotonin, not 5-HTP, increased both glucose and insulin concentrations for 1 h post-treatment (Watanabe et al 2014). This indicates that serotonin may act differently depending on the stage of the energy balance of the animal.…”
Section: Discussionmentioning
confidence: 87%
“…I.v. administration of serotonin to wethers also increased NEFA concentrations 1 h post-treatment, but concentrations then returned to baseline (Watanabe et al 2014). This suggests that even though we administered a serotonin precursor and not serotonin itself in the present study, the effects on NEFA concentrations would not have been long-lasting either way.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, Weaver et al (2016) and Hernández-Castellano et al (2017) demonstrated that the infusion of the 5-HT precursor 5-hydroxytryptophan (5-HTP) during the last days before parturition improved blood calcium concentrations around parturition. Additionally, 5-HT has been shown to influence several metabolites related to glucose and lipid metabolism such as glucose, insulin, triglyceride, cholesterol, and fatty acid concentrations in mice (Sugimoto et al, 1990;Watanabe et al, 2010) and sheep (Watanabe et al, 2014). Moreover, 5-HT promotes the proliferation and activation of B cells in mice (Iken et al, 1995), and therefore the IgG concentration could also be affected by the increased 5-HT concentration in blood.…”
Section: Introductionmentioning
confidence: 99%
“…Ruminants absorb little glucose and have no glucokinase activity in the liver, and nearly all of their glucose needs must be compensated by gluconeogenesis. Propionate is the principal source of carbon for glucose synthesis in liver, which meets 85%-90% of the body glucose requirements in sheep (Catunda et al, 2013;Watanabe et al, 2014). Alfalfa hay had a more effective role than sodium propionate on calf performance and rumen development (Beiranvand et al, 2014).…”
Section: Discussionmentioning
confidence: 99%